Реалізація концепції національної держави в сучасному світовому політичному просторі. - Тельнік, М.В.; Тельник, М.В.; Tel'nik, M. (My University, 2011)
The problems of functioning of nationally-state conception of public power realization are examined, in the context of changes which take place in modern outer political space. Attention applies on appearance of new organizational models of national states, capable to ﬂ exibly adapt oneself to quickly changing political terms.
Тельнік, М.В. Реалізація концепції національної держави в сучасному світовому політичному просторі. / М.В.Тельнік // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 43. С.153 - 159.
Keywords: Політичний простір; Поняття "національна держава"; Концепції національної держави; Національна держава в сучасному політичному просторі; Национальное государство в современном политическом пространстве; Концепции национального государства; Понятие "национальное государство"; Политическое пространство